Decolonizing Judeans: “Jewish-Indigeneity” and the (Re)Articulation of Decolonial Language - Molot, Jordan (Arc)

(untitled) (McGill School of Religious Studies, 2023)
The confluence of decolonization and the Anglo-American study of religion has generally followed a mode of critical self-reflection which aims to illuminate, problematize, and undo the field’s colonial contours. While crucial to decolonial processes within the academy, less appreciated or understood are the ways in which decolonial language has been invoked across a far broader social landscape, often indexing a range of political commitments and aspirations that depart considerably from more conventional decolonial frameworks. More often than not, such articulations are either rejected as fraudulent or cast off as mischaracterization of more noble decolonial projects. Using Jewish and Zionist communal discourses as a case study, this essay instead proposes to take seriously these articulations through a deeper inquiry into its undergirding religious, historical, and theological logics. In thinking through such orthogonal transformations of putatively decolonial claims, we may thereby arrive at a more capacious theoretical model that can organize divergent (and often contradictory) modes of decolonial interpretation by a range of social actors.